Abernethy Malformation in Combination with Gilbert’s Syndrome - N. B. Gubergrits; E. L. Bondar; E. A. Dyadyk; E. V. Berezhnaya; Yu. E. Chirkov; N. V. Byelyayeva; G. M. Lukashevich; T. L. Mozhyna (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. To present a clinical case of the Abernethy syndrome.Key points. Abernethy syndrome is a rare vascular anomaly associated with a congenital absence of the portal vein, as a result of which portal blood from the intestines and spleen drains directly into the systemic circulation bypassing the liver though a complete or partial shunt. In the vast majority of cases, Abernethy syndrome is manifested during the newborn period by jaundice syndrome, hypergalactosemia and encephalopathy. In rare cases, this vascular malformation is diagnosed in older patients during ultrasound screening. A 31 year-old patient sought medical attention with the complaints of sleep disturbance and fatigue. The conducted instrumental observation revealed echo-signs of malformation (agenesia) of the portal vein, which was further confirmed by both X-ray-contrast computed tomography and the pathohistological analysis of liver biopsy slides. The genotype UGT1A1•28 confirmed Gilbert's syndrome. Neutropenia (0.8 × 109/L) with a drop in the level of segmented neutrophils up to 27% was regarded as shunt neutropenia. Number connection test confirmed shunt encephalopathy. Conservative therapy for correcting hepatic encephalopathy was prescribed, followed by a dynamic monitoring of the patient’s condition.Conclusion. Diagnosis of Abernethy malformation is important for choosing the right treatment for the timely correction of complications of the disease and early detection of adenoma or hepatocellular carcinoma.